Pengaruh Kepemimpinan, Kepuasan Kerja, dan Motivasi terhadap Kinerja Pegawai pada Dinas Pemberdayaan Masyarakat dan Desa (Dispermades) Kabupaten Karanganyar - Endika Yusuf Cahyo Purnomo; Asih Handayani (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to analyze the significance of the influence of leadership, job satisfaction and motivation on the performance of Karanganyar Regency Dispermades employees. This research uses qualitative and quantitative data types. The data source used is the acquisition of primary data and secondary data. The population in this study was 40 employees of the Karanganyar Regency Dispermades, so the sampling technique in this study used a census technique, so that the entire population was sampled. The data analysis techniques used in this research are descriptive analysis, multiple linear regression analysis, t test, F test, and coefficient of determination (R2). The results of this research show that leadership (X1) has a significant effect on the performance of Karanganyar Regency Dispermades employees, thus the first hypothesis is proven to be true. Job satisfaction (X2) has no significant effect on the performance of Karanganyar Regency Dispermades employees, thus the second hypothesis is not proven true. Motivation (X3) has a significant effect on the performance of Karanganyar Regency Dispermades employees, thus the third hypothesis is proven to be true. The results of the F test show a significance value of 0.000, which means the model is correct in predicting the influence of leadership, job satisfaction and motivation on the performance of Karanganyar Regency Dispermades employees. The R2 test result is 0.915, meaning that the contribution of the leadership, job satisfaction and motivation variables to employee performance is 91.5%, the remainder (100% - 91.5%) = 8.5% is explained by other variables outside the model, for example discipline work, work environment, rewards, etc.